An optically pumped atomic clock based on a continuous slow cesium beam - Xie, Weibin; Wang, Qing; He, Xuan; Yuan, Zhichao; Fang, Shengwei; Chen, Nan; Xiong, Zezheng; Zhang, Jun’an; Qi, Xianghui; Li, Shaoguang; Chen, Xuzong (Frontiers in Physics, 2022)
Herein, we report the scheme of an optically pumped atomic clock based on a cold cesium atomic beam source. We propose the laser system and physical mechanism of this atomic clock, wherein the atomic beam travels in an upper parabolic trajectory, thereby eliminating the light shift effect. In the experiments, when the length of the free evolution region is 167 mm, the line width of the Ramsey fringe is 37 Hz. When the expected signal-to-noise ratio of the Ramsey fringe that can be achieved is 36000, the expected short-term frequency stability is about 3.6E−14/√τ, which is significantly higher than that of a conventional optically pumped cesium clock of similar volume.